Zinc Supplementation in Very Low Birth Weight Infants: A Randomized Controlled Trial - Sahin, Suzan; Sari, Fatma N.; Bidev, Duygu; Bozkurt, Ozlem; Dizdar, Evrim A.; Oguz, Serife S. (American Journal of Perinatology, 2023)
Objective Preterm infants have high zinc (Zn) requirements and are generally believed to be in a negative Zn balance in the early period of life. In this study, we aimed to investigate the effect of high-dose Zn supplementation in very low birth weight (VLBW: infants with birth weight < 1.5 kg) infants on feeding intolerance and development of mortality and/or morbidities including necrotizing enterocolitis (NEC) and late-onset sepsis (LOS).Study Design This is a prospective randomized trial. VLBW preterm infants with gestational age of <32 weeks were randomly allocated on the seventh day of life to receive extra amount of supplemental Zn along with the enteral feedings (9 + 3 mg), besides regular low-dose supplementation (3 mg), from enrollment until discharge. Outcome measures were feeding intolerance, NEC (stage ≥ 2), LOS, and mortality.Results A total of 195 infants (97 from study group and 98 from control group) were analyzed. A total of 46 (47.4%) infants in the study group and 64 (65.3%) infants in the control group ended up with feeding intolerance (p = 0.012). NEC was observed in 11 infants (11.2%) in the control group and only 1 infant (1%) in the study group (p = 0.003). There was a negative correlation between high-dose Zn supplementation and number of culture-proven LOS episodes (p = 0.041). This significance was also present for clinical sepsis, being higher in the control group (p = 0.029). No relationship between high-dose Zn supplementation and mortality and other morbidities (hemodynamically significant patent ductus arteriosus, bronchopulmonary dysplasia, retinopathy of prematurity, and severe intraventricular hemorrhage) was observed.Conclusion Zn supplementation for VLBW infants is found to be effective to decrease feeding intolerance, NEC, and LOS episodes in this vulnerable population. Current data support the supplementation of VLBW infants with higher than regular dose of Zn.Key Points
Keywords: neonatal sepsis; zinc; feeding intolerance; preterm infant